Polyamine metabolism dysregulation contributes to muscle fiber vulnerability in ALS - Veronica Ruggieri; Silvia Scaricamazza; Andrea Bracaglia; Chiara D’Ercole; Cristina Parisi; Paolo D’Angelo; Daisy Proietti; Chiara Cappelletti; Alberto Macone; Biliana Lozanoska-Ochser; Marina Bouchè; Lucia Latella; et al. (Cell Reports)
Summary: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease causing progressive paralysis due to motor neuron degeneration with no curative therapy despite extensive biomedical research. One of the primary targets of ALS is skeletal muscle, which undergoes profound functional changes as the disease progresses. To better understand how altered innervation interferes with muscle homeostasis during disease progression, we generated a spatial transcriptomics dataset of skeletal muscle in the SOD1G93A mouse model of ALS. Using this strategy, we identified polyamine metabolism as one of the main altered pathways in affected muscle fibers. By establishing a correlation between the vulnerability of muscle fibers and the dysregulation of this metabolic pathway, we show that disrupting polyamine homeostasis causes impairments similar to those seen in ALS muscle. Finally, we show that restoration of polyamine homeostasis rescues the muscle phenotype in SOD1G93A mice, opening new perspectives for the treatment of ALS.